Fluorinated poly(arylene ether ketone)s for high temperature dielectrics. (28th January 2016) - Shaver, Andrew T.; Yin, Kezhen; Borjigin, Hailun; Zhang, Wenrui; Choudhury, Shreya Roy; Baer, Eric; Mecham, Sue J.; Riffle, J.S.; McGrath, James E.
Abstract: There is a need for polymeric capacitors with improved energy storage density and thermal stability. In this work, the effect of polymer molecular structure and symmetry on Tg, breakdown strength, and relative permittivity were investigated. A systematic series of four amorphous poly(arylene ether ketone)s were compared. Two of the polymers had symmetric bisphenols while the remaining two had asymmetric bisphenols. Two contained trifluoromethyl groups while the other two had methyl groups. The symmetric polymers had Tg 's of approximately 160 °C while the asymmetric polymers showed higher Tg 's near 180 °C. The symmetric polymers had breakdown strengths near 380 kV/mm at 150 °C. The asymmetric counterparts had breakdown strengths near 520 kV/mm even at 175 °C, with the fluorinated polymers performing slightly better in both cases. The non-fluorinated polymers had higher relative permittivities than the fluorinated materials, with the asymmetric polymers being better in both cases. Graphical abstract: Highlights: Four poly(arylene ether ketone)s with varied symmetry and fluorination were compared. Tg, breakdown strength, and relative permittivity were compared. The asymmetric polymers performed better in all three categories. Fluorine increased Tg and breakdown strength but decreased relative permittivity. Asymmetric fluorine increased relative permittivity relative to symmetric fluorine.